1998
DOI: 10.1094/mpmi.1998.11.12.1196
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Resistance Gene-Mediated Defense Responses in Arabidopsis thaliana Plants Carrying a Mutation in CPR5

Abstract: In resistant plants, pathogen attack often leads to rapid activation of defense responses that limit multiplication and spread of the pathogen. To investigate the signaling mechanisms underlying this process, we carried out a screen for mutants in the signaling pathway governing resistance in Arabidopsis thaliana to the bacterial pathogen Pseudomonas syringae. This involved screening for suppressor mutations that restored resistance to a susceptible line carrying a mutation in the RPS2 resistance gene. A mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 53 publications
3
83
0
1
Order By: Relevance
“…Effect of eds1 on defense-related gene expression in the cpr mutants cpr1, cpr5 and cpr6 plants constitutively express the PR genes PR1, PR2 (BGL-2) and PR5, which are markers for SAR (Boch et al, 1998;, Bowling et al, 1997Clarke et al, 1998). Also, cpr5 and cpr6 induce expression of PDF1.2 mRNA, a marker of JA/ET-dependent signaling.…”
Section: Characterization Of the Cpr Eds1 Double Mutantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effect of eds1 on defense-related gene expression in the cpr mutants cpr1, cpr5 and cpr6 plants constitutively express the PR genes PR1, PR2 (BGL-2) and PR5, which are markers for SAR (Boch et al, 1998;, Bowling et al, 1997Clarke et al, 1998). Also, cpr5 and cpr6 induce expression of PDF1.2 mRNA, a marker of JA/ET-dependent signaling.…”
Section: Characterization Of the Cpr Eds1 Double Mutantsmentioning
confidence: 99%
“…The pleiotropic nature of cpr5 suggests a complex interplay of signals that undoubtedly complicates genetic epistasis studies (Boch et al, 1998;Bowling et al, 1997). We found that initiation of lesions (Figure 2a), pathogen resistance ( Figure 4) and SA accumulation ( Figure 5) in cpr5 eds1 plants resembles that in cpr5 or cpr5 EDS1 lines.…”
Section: Salicylic Acid Signaling Antagonizes Pdf12 Expression In Cpr6mentioning
confidence: 99%
See 1 more Smart Citation
“…The gene was initially identified in screens for mutants with enhanced disease resistance. 2,3 Several more cpr5 alleles were subsequently identified in screens for mutants with altered trichome development, 4 dark induced senescence (hys1 alleles) 5 and ethyleneinduced senescence (old1 alleles). 1,6 So far, described alterations in cpr5 mutants include (1) enhanced constitutive expression of PR genes, (2) elevated salicylic acid and jasmonic acid levels, (3) hypersensitivities to sugar, ABA, ethylene and jasmonic acid, (4) accelerated leaf senescence, (5) spontaneous lesion mimic cell death, (6) defective cell proliferation, endoreduplication and trichome development, (7) reduced plant growth and reproduction fecundity.…”
Section: The Pleiotropic Phenotypes Of Cpr5 Mutationsmentioning
confidence: 99%
“…1,6 So far, described alterations in cpr5 mutants include (1) enhanced constitutive expression of PR genes, (2) elevated salicylic acid and jasmonic acid levels, (3) hypersensitivities to sugar, ABA, ethylene and jasmonic acid, (4) accelerated leaf senescence, (5) spontaneous lesion mimic cell death, (6) defective cell proliferation, endoreduplication and trichome development, (7) reduced plant growth and reproduction fecundity. [1][2][3][4][5][6][7] Thus, cpr5 mutations possess pleiotropic phenotypes indicating that CPR5 is an essential-for-life gene in Arabidopsis.…”
Section: The Pleiotropic Phenotypes Of Cpr5 Mutationsmentioning
confidence: 99%